"The Sky Is Hidden": On the Opening Up of Language and National Borders. Issue 1 (2nd January 2019) - Magee, Paul; Isayev, Elena; Hussaini, Aref
Abstract : The article comprises a series of microessays, initially troped around three artworks by Cildo Mereiles, Rene Magritte, and Georges Perec. Each serves to problematize the links between geographical landscapes and entities as abstract and historically recent as nation-states. These essays are numbered in the fashion of bureaucratic documents (either processed or awaiting decision). Interspersed through them are photographic images of dilapidated and largely boarded-up houses, taken just kilometres from the Moria Refugee camp on Lesbos. The writing, meanwhile, turns from spatially subversive, contemporary artworks to consider a discourse on language and its role in creating space, from a time well prior to nation-states. Moments in Varro and Cicero bring out the historicity, and with that the fragility, of current ways—"by birth, " "sovereign soil, " "naturalization"—of linking terrain to territory, bodies to place. The article concludes with a discussion of intellectual strategy, via meditation on (the opening up of) the origins or words and geographies.